Reviving Bedlinen: User Expectations, Use-Life, and Repair Practices in Australia - Peters, Emma (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
This paper considers the relationship between user expectations of domestic bedlinen, product use-life and repair engagement within an Australian context. Bedlinen, in this instance, includes flat and fitted sheets, pillowcases, and quilt covers - also known as duvet covers, or in Australia, doona covers. There is limited data on this specific textile product within sustainability and circularity research. This paper discusses findings from the survey, Bedlinen and Sustainability (2023), which includes questions focused upon attitudes and behaviour regarding bedlinen purchase, use, care, repair, reuse and disposal. Key findings are identified and are discussed as factors that directly impact the use-life of bedlinen. These include laundering choices, emotional durability, change of mattress sizes, expectations of comfort, maintaining original condition, and repair challenges.